Selective brain regional changes in lipid profile with human aging - Natalia Mota-Martorell; Pol Andrés-Benito; Meritxell Martín-Gari; José Daniel Galo-Licona; Joaquim Sol; Anna Fernández-Bernal; Manuel Portero-Otín; Isidro Ferrer; Mariona Jove; Reinald Pamplona (GeroScience, 2022)
Fatty acids are key components in the structural diversity of lipids and play a strategic role in the functional properties of lipids which determine the integrity of neuronal and glial cell membranes, the generation of lipid signaling mediators, and the chemical reactivity of acyl chains. The present study analyzes using gas chromatography the fatty acid profiles of 13 regions of the human central nervous system in healthy individuals ranging from 40 to 80 years old. The outcomes suggest the existence of general traits in fatty acid composition such as an average chain length of 18 carbon atoms, high monounsaturated fatty acid content, and predominance in polyunsaturated fatty acids of those of series n-6 over series n-3 which are shared by all brain regions regardless of age. Our results also show a general sustained and relatively well-preserved lipid profile throughout the adult lifespan in most studied regions (olive, upper vermis, substantia nigra, thalamus, hippocampus, putamen, caudate, occipital cortex, parietal cortex, entorhinal cortex, and frontal cortex) with minor changes that are region-dependent. In contrast, of particular relevance is the involvement of the inferior temporal cortex and cingulate cortex. It is proposed that during normal human brain aging, the lipid profile is resistant to changes with age in most human brain regions to ensure cell survival and function, but some particular regions involved in specific memory domains are greatly affected.

Tau Protein as a New Regulator of Cellular Prion Protein Transcription - Laia Lidón; Cristina Vergara; Isidro Ferrer; Félix Hernández; Jesús Ávila; Jose A. del Rio; Rosalina Gavín (Molecular Neurobiology, 2020)

Wnt Signaling Alterations in the Human Spinal Cord of Amyotrophic Lateral Sclerosis Cases: Spotlight on Fz2 and Wnt5a - Carlos González-Fernández; Pau Gonzalez; Pol Andres-Benito; Isidro Ferrer; Francisco Javier Rodríguez (Molecular Neurobiology, 2019)

iPS Cell Cultures from a Gerstmann-Sträussler-Scheinker Patient with the Y218N PRNP Mutation Recapitulate tau Pathology - Andreu Matamoros-Angles; Lucía Mayela Gayosso; Yvonne Richaud-Patin; Angelique di Domenico; Cristina Vergara; Arnau Hervera; Amaya Sousa; Natalia Fernández-Borges; Antonella Consiglio; Rosalina Gavín; Rakel López de Maturana; Isidro Ferrer; et al. (Molecular Neurobiology, 2018)

Erratum to: Involvement of Cellular Prion Protein in α-Synuclein Transport in Neurons - Laura Urrea; Miriam Segura-Feliu; Masami Masuda-Suzukake; Arnau Hervera; Lucas Pedraz; José Manuel García-Aznar; Miquel Vila; Josep Samitier; Eduard Torrents; Isidro Ferrer; Rosalina Gavín; Masato Hagesawa; et al. (Molecular Neurobiology, 2018)

Involvement of Cellular Prion Protein in α-Synuclein Transport in Neurons - Laura Urrea; Miriam Segura-Feliu; Masami Masuda-Suzukake; Arnau Hervera; Lucas Pedraz; José Manuel García Aznar; Miquel Vila; Josep Samitier; Eduard Torrents; Isidro Ferrer; Rosalina Gavín; Masato Hagesawa; et al. (Molecular Neurobiology, 2018)

Reelin Expression in Creutzfeldt-Jakob Disease and Experimental Models of Transmissible Spongiform Encephalopathies - Agata Mata; Laura Urrea; Silvia Vilches; Franc Llorens; Katrin Thüne; Juan-Carlos Espinosa; Olivier Andréoletti; Alejandro M. Sevillano; Juan María Torres; Jesús Rodríguez Requena; Inga Zerr; Isidro Ferrer; et al. (Molecular Neurobiology, 2017)

Wnts Are Expressed in the Ependymal Region of the Adult Spinal Cord - Carlos Gonzalez-Fernandez; Angel Arevalo-Martin; Beatriz Paniagua-Torija; Isidro Ferrer; Francisco J. Rodriguez; Daniel Garcia-Ovejero (Molecular Neurobiology, 2017)

MicroRNA Expression in the Locus Coeruleus, Entorhinal Cortex, and Hippocampus at Early and Middle Stages of Braak Neurofibrillary Tangle Pathology - Franc Llorens; Katrin Thüne; Pol Andrés-Benito; Waqas Tahir; Belén Ansoleaga; Karina Hernández-Ortega; Eulàlia Martí; Inga Zerr; Isidro Ferrer (Journal of Molecular Neuroscience, 2017)

Dietary Lipid Unsaturation Influences Survival and Oxidative Modifications of an Amyotrophic Lateral Sclerosis Model in a Gender-Specific Manner - Daniel Cacabelos; Victoria Ayala; Omar Ramírez-Nunez; Ana Belen Granado-Serrano; Jordi Boada; Jose C. E. Serrano; Rosanna Cabré; Gisela Nadal-Rey; Maria Josep Bellmunt; Isidro Ferrer; Reinald Pamplona; Manuel Portero-Otin (NeuroMolecular Medicine, 2014)

Methyl- and acetyltransferases are stable epigenetic markers postmortem - Camelia Maria Monoranu; Edna Grünblatt; Jasmin Bartl; Andrea Meyer; Manuela Apfelbacher; Daniela Keller; Tanja M. Michel; Safa Al-Saraj; Andrea Schmitt; Peter Falkai; Wolfgang Roggendorf; Jürgen Deckert; et al. (Cell and Tissue Banking, 2011)

Small deletions disturb desmin architecture leading to breakdown of muscle cells and development of skeletal or cardioskeletal myopathy - Anna Kaminska; Sergei V. Strelkov; Bertrand Goudeau; Montse Oliv; Ayush Dagvadorj; Anna Fidzianska; Monique Simon-Casteras; Alexey Shatunov; Marinos C. Dalakas; Isidro Ferrer; Hubert Kwiecinski; Patrick Vicart; et al. (Human Genetics, 2004)